Importancia del desayuno escolar en el cuidado de la salud y nutrición en los niños y niñas de educación general básica de la Unidad Educativa “Ana Páez” de la ciudad de Latacunga - Pila Chicaiza, Karla Elizabeth (2016)
This research focuses on the orientation about how the educational community should be fed in order to improve their quality of life into the childhood of Ana Paez, Educative Unit because there is no alternative to change the school breakfast. It is noteworthy that health and nutrition are important factors of growth and development for each student, it helps to optimize the process of mutual leaming. The methodology has shown the reality of the problem through fíeld research, the results obtained by the researchers allowed to have a clear visión of how to bring their food daily….